STUDI PENGEMBANGAN PEMANFAATANEMBUNG KALIAJI SEBAGAI SUPLAI AIR PDAM SLEMAN - Anis Mulyati Cholifah, Ratna Septi Hendrasari (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2014)
Water needs will be getting increases along with increasing population and the needs of human life. An effort to solve the problem is to accommodate water in embung. Embung Kaliaji is located in the hamlet sangurejo administration, wonokerto village, turi , sleman. Embung Kaliaji used the citizens to aquaculture, irrigation rice fields, and plantation. The development of the use of the potential of water resources that one of them are as a source of raw PDAM water. Kaliaji embung water will be utilized to increase the supply of PDAM water on sleman so it can meet the needs of the PDAM on water. In this research is analyzing the availability of water at embung Kaliaji by means of change rain to discharge use the mock model. An analysis of the needs of water based on the water needs of the rice plant , vegetables , and salak. The development of the utilization of feasibility analysis embung Kaliaji to PDAM sleman is conducted by seeing water balance who described the conditions the availability of water and high demand for water. Based on the analysis , that the availability of water obtained more experienced a period of surplus with the average 81,39 liter/second. The availability of water is highest occurred in february with the middle of the second month of 142,72 liters per second , while the availability of the water lowest is in january the middle of the first month of 9,18 liters per second. The water needs for irrigation highest occurring at the beginning to the middle of july first worth 11,65 liters per second, with the type of vegetable crops and salak the needs of water while the lowest is in the third week until the end of december worth 0.2 liters per second, with the type of rice plants. Based on the water analysis balance , by comparing the availability of water and demand of water , be seen that the development of the use of technical embung Kaliaji to the supply of PDAM water on sleman worthy of developed , by the limitation of the collection in february mid- up to december amounting to 10 liters per second , in january up to february middle ages of 1-5 liters per second.Key words: Kaliaji, PDAM sleman, water